Monetary policy and TIPS yields before the crisis - Stefan Gerlach; Laura Moretti (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
We make three points. First, the decade before the financial crisis in 2007 was characterized by a collapse in the yield on TIPS. Second, estimated VARs for the federal funds rate and the TIPS yield show that while monetary policy shocks had negligible effects on the TIPS yield, shocks to the latter had one-to-one effects on the federal funds rate. Third, these findings can be rationalized in a New Keynesian model.
urn:nbn:de:hebis:30-115381
Keywords: E43; E52; E58; 330; Monetary Policy; Long Real Interest Rates; TIPS; Finanzmarkt; Geldpolitik; Wertpapierhandel; Indexierung; Zins; Kapitalertrag; Finanzmarktkrise; USA